DEVELOPMENT OF LKPD BASED ON PROBLEM BASED LEARNING MODEL FOR SMP CLASS VII ON ENVIRONMENTAL POLLUTION MATERIAL - Neng Liva Yanti; Skunda Diliarosta (Department of Science Education, 2023)
The background of this research is because of the problems encountered, namely the lack of interest and motivation to learn students, learning models are less varied and have not used teaching materials in the form of LKPD. This study aims to determine the validity and practicality of LKPD-based learning model Problem Based Learning for SMP class VII on environmental pollution material. This research is a type of research and development (R & D) with the ADDIE development model consisting of 5 stages, namely analysis, design, development, implementation, and evaluation. Due to time and cost limitations, this research was only carried out until the development stage. The research instrument consisted of an interview sheet, a validity questionnaire and a practicality questionnaire. The data obtained were analyzed using the moment kappa formula. The results showed that the LKPD based on the Problem Based Learning learning model was categorized as valid with an average score of 0.813. While the results of the practicality test are categorized as practical with an average score of 0.819 teacher responses and 0.845 student responses. Based on the results of the study, it can be concluded that the LKDP based on the Problem Based Learning model for SMP class VII on environmental pollution material is categorized as valid and practical.